(3GdTLQI GdEdgjI aj GdYdhe GdQHGfjIs - (3TeS GdOjf eMeO GdTgQRhQjs ((3eMeO Hf SdeGf Hf Ydi GdCSOj s)
(3ChdgG (B:s
(3jHOC HGdaUd GdChd ai UOQ GdMceI s
(3BNQgG (B:s
(3hdG jJcGSd aEf GdhbJ Sja bGWY aEf GdCjGe JeVi hdG JYhO JeJ GdcQGQjS s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(3233) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs